Repurchase Intention of Sweet Bread Products in Tangerang (A Study on The ROTI X) - Dede Wahidin Jafar; Arif Imam Suroso; Asep Taryana (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The production of bread is predominantly dependent on wheat flour as its core input. Therefore, volatility and inflationary trends in the price of this commodity present a persistent operational and strategic challenge for bakery companies, directly affecting their cost structures, revenue streams, and ultimately, their pricing strategies for end consumers. Within this competitive and cost-sensitive environment, understanding the determinants of consumer purchase behavior is paramount. This behavior is not monolithic but is influenced by a complex interplay of determinants, notably those related to price perception (e.g., value, fairness) and socio-psychological factors captured by behavioral theories. A precise understanding of these mechanisms is critical for businesses to navigate market challenges and cultivate lasting consumer loyalty through increased repurchase intention.Purpose: This study aims to examine the influence of product price image, price sensitivity, and the Theory of Planned Behavior (TPB) on repurchase intention and to investigate the mediating role of perceived value in the relationship between product price image and repurchase intention.Design/methodology/approach: This study employed a purposive sampling technique, collecting data from 225 respondents who met the eligibility criteria: individuals aged at least 17 years (or born in 2007 or later) and who had purchased Roti X within the last six months. The research was geographically limited to the Tangerang area. The collected data were analyzed using descriptive statistics and Structural Equation Modeling (SEM).Findings/Result: The findings indicate that the majority of respondents purchased bread more than five times per month, typically consuming 1–2 loaves per week. The primary reasons cited were taste, affordable price, and recommendations from close acquaintances. The SEM-PLS analysis revealed several key relationships. Perceived value demonstrated a significant direct influence on repurchase intention. In contrast, the product’s price image did not exhibit a significant direct effect. However, the analysis confirmed that perceived value acts as a significant mediating variable between product price image and repurchase intention. Furthermore, all constructs from the Theory of Planned Behavior (TPB) attitude, subjective norm, and perceived behavioral control significantly influenced repurchase intention, with perceived behavioral control emerging as the dominant factor. Finally, price sensitivity was found not to be a significant moderating variable in the relationships between product price image/perceived value and repurchase intention.Conclusion: The enhancement of perceived value, the preservation of a favorable price image, the assurance of price competitiveness, and the improvement of product accessibility constitute critical determinants in fostering repurchase intention.Originality/value (State of the art): This study employs a distinct approach by integrating the Theory of Planned Behavior (TPB) with product price image and perceived value to analyze repurchase intention of sweet bread. Keywords:   perceived value, price sensitivity, product price image, repurchase intention, theory of planned behavior (TPB)